TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA DI PONDOK PESANTREN AL-MUNAWWIR KOMPLEK Q KRAPYAK YOGYAKARTA - Ariyani, Hera; Ekawati (MEDIA ILMU KESEHATAN, 2015)
Background: Anemia is a nutritional problem that is frequently experienced by adolescence. The prevalence in Indonesian female teenager in 2013 is categorized according to age, 5-14 years old is 26,4%, 15-24 years old is 18,4%, 25-34 is 16,9%, 35-44 years old is 18,3%, 45-54 years old is 20,1%, 55-64 years old is 25,0%, 65–74 years old is 34,2%. Goal: To explore the knowledge level of female teenager at Islamic boarding house of Al-Munawwir Block Q Krapyak Yogyakarta about anemia. Method: This was a descriptive quantitative research. Samples were selected with total sampling method. The number of sample were 38 female teenagers at the islamic boarding house of Al-munawwir block Q Krapyak. Data collecting is conducted with a closed-questionnaire and data analysis was with univariat analysis. Result: The knowledge level of female teenager about anemia mostly was at good category (44,7%), knowledge level of female teenager about anemia definition was mostly at adequate category (42,1%), knowledge level of female teenager about the cause of anemia was mostly at adequate category (39,5%) and deficient (39,5%), knowledge level of female teenager about the effect of anemia was mostly at good category (47,4%), knowledge level of female teenager about the prevention of anemia was mostly at good category (78,9%), knowledge level of female teenager about the treatment of anemia was mostly at deficient category (65,8%). Conclusion: The knowledge level of female teenager about anemia at Islamic boarding house of Al- munawwir Krapyak was at good category. Keywords: Knowledge level, anemia, female teenager